Pemberian NPK Mutiara 16:16:16 dan Pupuk Kandang Ayam Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L) - Wina Novita Ria; Nurma Ani; Dermawan Hutagaol (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2026)
Shallots, or in its Latin name is Allium ascalonicum L is a type of bulb that is often used as a cooking spice, especially those originating from Southeast Asia. At the same time, it is also an important vegetable horticultural commodity because it is very necessary for household consumption and the food industry. This study aims to evaluate the effect of the application of NPK Mutiara 16:16:16 fertilizer and chicken manure on the growth and production of shallots (Allium ascalonicum L). A Factorial Randomized Block Design was chosen in the study with the provision of two factors studied and three replications. The two factors are the application of NPK Mutiara 16:16:16 fertilizer (F) at three levels (F0 = control, F1 = 40 g plot-1, and F2 = 80 g plot-1), and the application of chicken manure (K) as the second factor with four levels (K0 = control, K1 = 0.75 kg plot-1, K2 = 1.5 kg plot-1, and K3 = 2.25 kg plot-1). The parameters assessed included plant height (cm), number of tillers per sample, number of tubers per sample, number of tubers per plot, tuber weight per sample, and tuber weight per plot. The results showed that the use of NPK Mutiara 16:16:16 fertilizer did not significantly affect any of the parameters measured. Similarly, the use of chicken manure did not significantly impact any of the observed parameters. In fact, the interaction between the use of NPK Mutiara 16:16:16 and chicken manure did not significantly affect any of the observed parameters.